Effects caused by high-intensity interval training in sarcopenic elderly people (Research, Society and Development, 2024)
Sarcopenia represents a significant public health challenge, predominantly affecting elderly individuals. Preventive and therapeutic strategies often combine nutritional classes with regular physical activity programs. In this context, high-intensity interval training (HIIT) emerges as a promising intervention for improving muscle function in elderly people with sarcopenia. Therefore, the objective of the present study is to evaluate, through a literature review, the effects of high-intensity interval training (HIIT) on muscle strength, with a focus on the prevention and treatment of sarcopenia in the elderly. This study performed an integrative review to evaluate the impact of HIIT on muscle strength and its effectiveness in preventing and managing sarcopenia in older adults. The search included renowned databases, such as PubMed, Scopus, SPORTDiscus, and Web of Science, with a literary interval between 2017 and 2023, 224 studies were identified, of which five met the specific inclusion criteria. The results indicate that HIIT promotes improvements in body composition, and functional and cardiorespiratory capacity, and benefits in strength, quality, and muscular architecture, associated with hypertrophy in healthy elderly people. However, the methodological limitations of the literature, including the limited number of studies and the high risk to life, highlight the need for additional investigations to corroborate these findings.